A Case Report of Primary Amenorrhea Due to Imperforate Hymen with Hematocolpos and Hematometra: Diagnosis and Management - Zafira Yasmin Fadhila; Hana Fadila; Dani Setiawan (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: Imperforate hymen (IH) is a congenital anomaly of the female genital tract that causes obstruction of vaginal flow. This report aims to describe the clinical presentation of an imperforate hymen and the surgical approach used in the patient.Case Illustration: A 13-years-old girl presented to the obstetrics and gynecology clinic with the chief complaint of lower abdominal pain. Physical examination of the external genitalia revealed a bulging, bluish hymenal membrane. Pelvic ultrasonography showed findings consistent with hematocolpos and hematometra. A diagnosis of imperforate hymen was established. A hymenotomy was performed using a cruciate incision technique. Postoperative evaluation two weeks later demonstrated good wound healing without complications.Conclusion: Imperforate hymen should be identified and managed promptly to prevent complications. Hymenotomy using a cruciate incision technique is an effective therapeutic option with favorable clinical outcomes.Amenore Primer Akibat Himen Imperforata dengan Hematokolpos dan Hematometra: Diagnosis dan TatalaksanaAbstrakPendahuluan: Himen imperforata (HI) merupakan anomali kongenital saluran genitalia wanita yang menyebabkan obstruksi saluran vagina. Laporan ini bertujuan untuk mendeskripsikan himen imperforata dan pendekatan pembedahan pada pasien.Ilustrasi Kasus: Seorang perempuan usia 13 tahun datang ke poliklinik dengan keluhan utama nyeri perut bawah. Inspeksi genitalia eksterna menunjukkan himen menonjol berwarna kebiruan, dan gambaran hematokolpos pada ultrasonografi pelvis. Diagnosis himen imperforata ditegakkan. Tindakan himenotomi dilakukan dengan teknik insisi menyilang. Evaluasi dua minggu pascaoperasi menunjukkan penyembuhan yang baik tanpa komplikasi.Kesimpulan: Himen imperforata perlu diidentifikasi dan ditangani segera untuk mencegah komplikasi. Himenotomi dengan teknik insisi menyilang merupakan pilihan terapi efektif dengan hasil klinis yang baik.